Ah, sweet mystery of life stories - Dahl, Roald 1916-1990 (Knopf, 1990)
A collection of stories dating from the 1940's depicting life in an English village.
Keywords: Country life -- Fiction; Short stories; Short stories.; Villages -- Fiction.; England -- Fiction.